2018
DOI: 10.1093/mnras/sty2714
|View full text |Cite
|
Sign up to set email alerts
|

A consistent estimate for gravitational wave and electromagnetic transient rates

Abstract: Gravitational wave transients, resulting from the merger of two stellar remnants, are now detectable. The properties and rates of these directly relates to the stellar population which gave rise to their progenitors, and thus to other, electromagnetic transients which result from stellar death. We aim to estimate simultaneously the event rates and delay time distribution of gravitational wave-driven compact object mergers together with the rates of core collapse and thermonuclear supernovae within a single con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 93 publications
9
110
0
Order By: Relevance
“…We modify our method from Eldridge et al (2019) in two ways. First, to allow for uncertainties in the high redshift cosmic star formation history we adopt a star formation rate 1 http://bpass.auckland.ac.nz density as a function of redshift as follows, ψ(z) = 0.015…”
Section: Methods Observations and Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We modify our method from Eldridge et al (2019) in two ways. First, to allow for uncertainties in the high redshift cosmic star formation history we adopt a star formation rate 1 http://bpass.auckland.ac.nz density as a function of redshift as follows, ψ(z) = 0.015…”
Section: Methods Observations and Simulationsmentioning
confidence: 99%
“…In this expression the value of β determines how quickly the Universe becomes enriched with metals, Z, as a function of redshift z and how broad the metallicity distribution is at each redshift. While in Eldridge et al (2019) we used β = 2 here we allow this exponent to vary from 1 to 6. A higher β means the Universe was more quickly enriched, with a smaller metallicity scatter.…”
Section: Methods Observations and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this process occurs at low metallicity, the secondary can retain the angular momentum gained from mass transfer, and end its life as a rapidly spinning type Ic progenitor -a good candidate for producing a GRB. Eldridge et al (2019b) calculated the volumetric event rate of GRBs as a function of redshift, assuming that they arise solely from a quasi-homogeneous evolution (QHE) pathway (Yoon et al 2006;Cantiello et al 2007), using the BPASS stellar evolution and population synthesis code (Eldridge et al 2017). They found that although QHE stars could account for the observed GRB rate, there are significant uncertainties arising from luminosity function and beaming corrections.…”
Section: Introductionmentioning
confidence: 99%